Developmental aspects of male reproductive health: clinical studies on semen quality, cryptorchidism, and puberty - Rodprasert, Wiwat (fi=Turun yliopisto|en=University of Turku|, 2023)
Current evidence shows increasing rates of male reproductive disorders, including cryptorchidism, hypospadias, poor semen quality, decreased testosterone level, and testicular cancer. Therefore, studies on the physiology of the male reproductive system, and the current state of male reproductive health are necessary. In the first study, we followed the semen quality of young men for 10 years from the age of 19 years to see whether there are age-related changes in semen quality. In the second study, we compared the semen quality of young Finnish and Danish men to clarify possible differences between the countries. In the third study, we compared serum levels of reproductive hormones and insulin-like growth factor (IGF)-I) during puberty between individuals with and without a history of cryptorchidism to see whether a history of orchiopexy or delayed testicular descent is associated with alterations in the levels of these hormones. The first study showed that sperm concentration and total sperm count do not generally increase after 19 years, indicating that the maximum sperm production capacity is reached already in young adulthood. Sperm motility and morphology continue to improve after the age of 19 years. The second study showed that unlike in earlier studies, sperm concentrations, total sperm counts, and percentages of morphologically normal spermatozoa of Finnish and Danish men were now similar. However, Finnish men had better sperm motility. The third study showed that especially boys with a history of operated bilateral cryptorchidism had higher serum FSH and lower inhibin B levels than non-cryptorchid boys during puberty. These findings indicated an impaired Sertoli cell and/or germ cell function or number. Leydig cell function and the function of the growth hormone-IGF-I system were generally well-preserved during puberty in boys with a history of cryptorchidism.

--- Miehen lisääntymisterveyteen liittyvien ongelmien, kuten kivesten laskeutumattomuuden (piilokiveksisyyden), virtsaputken alahalkioisuuden, kivessyövän, heikentyneen siemennesteen laadun sekä alhaisen testosteronipitoisuuden, on raportoitu yleistyneen. Tämän vuoksi tarvitaan tutkimuksia miehen lisääntymiselimistön normaalista toiminnasta sekä miesten lisääntymisterveyden nykytilasta. Väitöskirjan ensimmäisessä osatyössä selvitettiin tapahtuuko 19-vuotiaiden miesten siemennesteen laadussa muutoksia 10 vuoden seurannan aikana. Toisessa osatyössä verrattiin suomalaisten ja tanskalaisten nuorten miesten siemennesteen laatua, jotta nähtäisiin onko maiden välillä eroa siemennesteen laadussa. Kolmannessa osatyössä verrattiin piilokives- ja verrokkiryhmien sukupuolihormonien ja insuliinin kaltaisen kasvutekijä I:n (IGF-I) pitoisuuksia läpi murrosiän. Tässä viimeisessä osatyössä haluttiin selvittää, liittyykö hoidettuun tai spontaanisti parantuneeseen piilokiveksisyyteen muutoksia murrosiän hormoni- ja kasvutekijätasoissa. Ensimmäisessä osatyössä todettiin, että siemennesteen siittiöpitoisuus ja siittiömäärä eivät yleisesti kasva 19. ikävuoden jälkeen. Tämä viittaa siihen, että maksimaalinen siittiötuotantokapasiteetti saavutetaan jo varhaisessa aikuisiässä. Toisessa osatyössä havaittiin, että toisin kuin aiemmissa tutkimuksissa, suomalaisten ja tanskalaisten nuorten miesten välillä ei ollut enää eroa siittiöpitoisuudessa, siittiöiden kokonaismäärässä eikä normaalien siittiöiden määrässä. Suomalaisten nuorten miesten siittiöt liikkuivat kuitenkin paremmin kuin tanskalaisten miesten siittiöt. Kolmannessa osatyössä havaittiin, että etenkin leikkaushoitoa vaatineeseen molemminpuoliseen piilokiveksisyyteen liittyi murrosiässä verrokkeja suurempi follikkelia stimuloivan hormonin pitoisuus ja verrokkeja pienempi inhibiini B:n pitoisuus. Nämä viittaavat vähentyneeseen Sertolin solujen ja/tai itusolujen toimintaan tai määrään. Murrosiän aikainen Leydigin solujen ja IGF-I-kasvuhormoni -akselin toiminta oli yleisesti ottaen normaalia piilokivesryhmässä.